Effects of Different Biochars on Pinus elliottii Growth, N Use Efficiency, Soil N2O and CH4 Emissions and C Storage in a Subtropical Area of China - LIN, Zhibin; LIU, Qi; LIU, Gang; COWIE, Annette L.; BEI, Qicheng; LIU, Benjuan; WANG, Xiaojie; MA, Jing; ZHU, Jianguo; XIE, Zubin (Pedosphere, 2017)
Intensive management of planted forests may result in soil degradation and decline in timber yield with successive rotations. Biochars may be beneficial for plant production, nutrient uptake and greenhouse gas mitigation. Biochar properties vary widely and are known to be highly dependent on feedstocks, but their effects on planted forest ecosystem are elusive. This study investigated the effects of chicken manure biochar, sawdust biochar and their feedstocks on 2-year-old Pinus elliottii growth, fertilizer N use efficiency (NUE), soil N2O and CH4 emissions, and C storage in an acidic forest soil in a subtropical area of China for one year. The soil was mixed with materials in a total of 8 treatments: non-amended control (CK); sawdust at 2.16 kg m−2 (SD); chicken manure at 1.26 kg m−2 (CM); sawdust biochar at 2.4 kg m−2 (SDB); chicken manure biochar at 2.4 kg m−2 (CMB); 15N-fertilizer alone (10.23 atom% 15N) (NF); sawdust biochar at 2.4 kg m−2 plus 15N-fertilizer (SDBN) and chicken manure biochar at 2.4 kg m−2 plus 15N-fertilizer (CMBN). Results showed that the CMB treatment increased P. elliottii net primary production (aboveground biomass plus litterfall) and annual net C fixation (ANCF) by about 180% and 157%, respectively, while the the SDB treatment had little effect on P. elliottii growth. The 15N stable isotope labelling technique revealed that fertilizer NUE was 22.7% in CK, 25.5% in the NF treatment, and 37.0% in the CMB treatment. Chicken manure biochar significantly increased soil pH, total N, total P, total K, available P and available K. Only 2% of the N in chicken manure biochar was available to the tree. The soil N2O emission and CH4 uptake showed no significant differences among the treatments. The apparent C losses from the SD and CM treatments were 35% and 61%, respectively; while those from the CMB and SDB treatments were negligible. These demonstrated that it is crucial to consider biochar properties while evaluating their effects on plant growth and C sequestration.